Sosialisasi & Pelatihan Karyawan tentang Laporan Keuangan Berdasarkan SAK ETAP - Thomas Averio; Arif Budi Satrio; Sisca Contesa; Theresia Contesa (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Employee turnover in a company necessitates the need for work adaptation so that the company's economic wheels can run as they should. Understanding the concepts and techniques of preparing financial reports, especially for new administration, finance and accounting staff, is very important. To get a common perception, all staff in this field need training. This is the background for carrying out socialization & training on financial reports based on SAK ETAP at PT Sumber Satwa Pertiwi. This activity was held boldly using lecture and discussion methods. The participants in this training were twenty staff in the administration, finance and accounting departments. The core implementation of this activity lasted for two days. Through carrying out this activity, it is hoped that participants will gain the same concepts and practical skills in preparing financial reports so that the financial reports presented are not misstated. Apart from that, it is hoped that participants can also understand the basics of preparing financial reports and the differences in SAK in Indonesia so that the process of preparing financial reports can be carried out by individuals who are considered skilled and produce good output.